Edukasi Tentang Pengolahan Sisa Kotoran Ayam Menjadi Pupuk Organik Yang Ramah Lingkungan Untuk Tanaman Mentimun di Desa Suka Makmur - Edisah Putra Nainggolan; Rifki Hamdani; Sa’diyah Anggraini Daulay; Shania Dwi Agitta br.Tarigan; Dinda Ramadhani Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
Chicken manure, produced by both broiler and laying hens, has a large capacity as an organic fertilizer. Its composition varies, depending on several factors, such as the ration given, the physiological nature of the chicken, and the condition of the cage, involving temperature and humidity. As a source of organic material, chicken manure has an important effect on the physical and chemical properties of the soil and plant growth. This manure is rich in nutrients and organic matter, with a relatively low water content. Chicken manure is a product produced by chickens as part of their digestive process, which also includes urine and other food waste. This manure plays an important role as a fertilizer, because it is rich in elements that support soil fertility, replacing nutrients that have been absorbed by plants. Manure, which comes from the manure of livestock such as chickens, horses, goats, sheep, and cows, has various benefits. In addition to adding nutrients to plants, manure also improves soil structure, increases humus and organic matter in the soil, and supports the growth of microorganisms in it.